The subunit of RNA N6-methyladenosine methyltransferase OsFIP regulates early degeneration of microspores in rice - Zhang, Fan; Zhang, Yu-Chan; Liao, Jian-You; Yu, Yang; Zhou, Yan-Fei; Feng, Yan-Zhao; Yang, Yu-Wei; Lei, Meng-Qi; Bai, Mei; Wu, Hong; Chen, Yue-Qin (PLoS genetics, 2019)
N6-Methyladenosine (m6A) RNA methylation plays important roles during development in different species. However, knowledge of m6A RNA methylation in monocots remains limited. In this study, we reported that OsFIP and OsMTA2 are the components of m6A RNA methyltransferase complex in rice and uncovered a previously unknown function of m6A RNA methylation in regulation of plant sporogenesis. Importantly, OsFIP is essential for rice male gametogenesis. Knocking out of OsFIP results in early degeneration of microspores at the vacuolated pollen stage and simultaneously causes abnormal meiosis in prophase I. We further analyzed the profile of rice m6A modification during sporogenesis in both WT and OsFIP loss-of-function plants, and identified a rice panicle specific m6A modification motif "UGWAMH". Interestingly, we found that OsFIP directly mediates the m6A methylation of a set of threonine protease and NTPase mRNAs and is essential for their expression and/or splicing, which in turn regulates the progress of sporogenesis. Our findings revealed for the first time that OsFIP plays an indispensable role in plant early sporogenesis. This study also provides evidence for the different functions of the m6A RNA methyltransferase complex between rice and Arabidopsis.